Improving measured health-related quality of life with outpatient high-dose methotrexate regimen among oncology patients with intracranial metastases: A systematic assessment - Heun Min; Elizabeth Weil; Maggie Nelson; John Charlson; Yee Chung Cheng; Lubna N Chaudhary; John Burfeind; Janet Retseck; Deepika Sriram; Sailaja Kamaraju (Archives of Nursing Practice and Care - Peertechz Publications, 2023)
Intracranial metastases including leptomeningeal disease are not uncommon in patients with metastatic solid tumor cancers, such as breast and sarcoma.  Treatment options are limited with disease progression on standard-of-care therapies, and high-dose Methotrexate (MTX) is offered for patients with well-preserved performance status. However, standard high-dose MTX treatment entails a lengthy hospitalization and close monitoring which can limit Quality of Life (QoL) for patients who already have multiple provider visits. The impact of high-dose MTX on patients' daily lives has not yet been qualitatively examined. As a quality improvement project, our team designed an outpatient high-dose protocol for patients who tolerated at least one cycle of inpatient high-dose MTX, and herein we describe the protocol and a quality survey with patients' feedback.  The purpose of this study is to explore and compare the influence of high-dose MTX treatments in two different settings - inpatient and ambulatory - on patients' QoL. Second, we aim to identify recurrent themes defining patients' perceived QoL and healthcare experiences. This study identified key QoL impacts that high-dose MTX treatments have on metastatic breast and sarcoma patients. Patients experienced decreased health-related burdens and improved social and psychosocial well-being associated with high-dose MTX treatment compared to standard inpatient treatment. This study provides an opportunity to identify recurrent thematic domains defining QoL in women with metastatic breast cancer.